Children's Experiences with School Lockdown Drills: A Pilot Study. Issue 3 (21st June 2021) - Bonanno, Rebecca; McConnaughey, Susan; Mincin, Jenny
Abstract: In response to the threat of school shootings, lockdown drills have become commonplace in K–12 schools throughout the United States. Educators, parents, and others continue to debate the potential disruptive and traumatizing impact drills have on children. A small number of quantitative studies have examined the effects of lockdown drills on students' perceptions of safety, preparedness for crises, and fear and anxiety. Less is known about children's actual lived experiences of lockdown drills. This pilot child-centered qualitative study explored how children ages eight to 11 thought and felt about their experiences of school lockdown drills. Fear was found to be their common emotional response to the drill and, to a lesser extent, so were feelings of safety, annoyance, and excitement. Although children were found to have good understanding of what to do in lockdown drills, they were not always clear about what the purpose of the drills was and what threats the drills were intended to protect against. These findings support professional and advocacy groups' recommendations for planning and implementing lockdown drills and offer original recommendations from children's points of view on ways to mitigate negative outcomes of drills for students.